Conjugation of approach fill with bridge and overbridge - A. L. Lanis; D. A. Razuvaev; P. O. Lomov (Вестник СибАДИ)
Questions of conjugation bridge, overbridge and viaducts with approach fill were considered. Reasons for the formation of residual deformations in the roadway identified, also It was considered applicable constructions. It was suggested construction of conjugation listed artificial structures with approach fill, consisting in reinforcement of the subgrade in the transition area concrete filling pile. The effectiveness was confirmed by estimations of elastic deflection of the roadway and research their changes along area of еhe proposed method of conjugation.